6a+2=7a-1

Simple and best practice solution for 6a+2=7a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+2=7a-1 equation:


Simplifying
6a + 2 = 7a + -1

Reorder the terms:
2 + 6a = 7a + -1

Reorder the terms:
2 + 6a = -1 + 7a

Solving
2 + 6a = -1 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
2 + 6a + -7a = -1 + 7a + -7a

Combine like terms: 6a + -7a = -1a
2 + -1a = -1 + 7a + -7a

Combine like terms: 7a + -7a = 0
2 + -1a = -1 + 0
2 + -1a = -1

Add '-2' to each side of the equation.
2 + -2 + -1a = -1 + -2

Combine like terms: 2 + -2 = 0
0 + -1a = -1 + -2
-1a = -1 + -2

Combine like terms: -1 + -2 = -3
-1a = -3

Divide each side by '-1'.
a = 3

Simplifying
a = 3

See similar equations:

| 3e-2=13e-62 | | 9-8g=31 | | -x-8=4x-38 | | xy+2x=300 | | -4-8x+9x=12 | | .33x+10=0.6 | | -6+3y=-15 | | 3e+16=13e-94 | | (2cosx+1)(cosx+1)=0 | | -x^2-4x+32.01=0 | | 60p+50= | | 7u=4u+9 | | (X+7)(x+1)=(x+1) | | 35=-4d+7 | | (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 | | -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 | | 4(3x-2)+4(x+1)=100 | | 7a+2a=18-9 | | 2=-3c+26 | | 3x+8x+4=12x+2 | | 8a+10=82 | | 2x+3-2(x-2)=-3(x+1)+22 | | 8n^2+8n=160 | | 3(X+20)=360 | | 0.92=0.4+0.1 | | 19+(-34)=2.8e+12 | | 8(2x+3)-(11x-4)=3 |

Equations solver categories